The role of human capital, innovation capability, accountability in improving performance: A mediation-moderation analysis - Hafiluddin, Aaqilatul Mumtaazah; Widiastuti, Harjanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to determine the effect of human capital on the performance of VOEs through innovation capability and moderated by the accountability public on VOEs in the province of Bangka Belitung and West Sumatra.Design/Methodology/Approach: The sample consisted of 152 VOEs from West Sumatra and Bangka Belitung. Data were analyzed using SEM-PLS with SmartPLS 4.0. This quantitative study used primary data from questionnaires distributed to VOE management in both provinces.Research findings: The results show that Human Capital has a direct impact on the performance of VOEs and their innovation capability. The Innovation Capability also has a direct effect on performance. In addition, human capital affects VOE performance through innovation capability. Public accountability can weaken the innovation capability on performance.Theoretical contribution/Originality: This research is a development of previous research by adding public accountability as a moderating variable that can affect the quality of performance that is not present in previous studies. Practitioner/Policy implication: This study's findings suggest that the management of VOEs can improve service quality and human resources to create innovation and performance, which is important for local governments to create a supportive environment for VOEs innovation. Research limitation/Implication: The limitation of this research is that it only focused on VOEs in the Provinces of Bangka Belitung and West Sumatra. This research also only uses social desirability research instruments. Future research should expand the research scope, conduct research using interviews or other methods, and add other variables such as social capital and transparency.